Multiplex polymerase chain reaction detection of Curvularia lunata, Bipolaris maydis, and Aureobasidium zeae in infected maize leaf tissues. (22nd July 2019) - Lu, Yuanyuan; Song, Yanbo; Xue, Zhiquan
Abstract: Multiplex polymerase chain reaction (PCR) is a method for simultaneous identification and detection of multiple pathogenic fungi, however, its complexity limits its application. To simplify the protocol and to improve the effectiveness, three‐level designs for six factors (three primers, Taq DNA polymerase, dNTP, Mg 2+ ) were constructed to optimize the multiplex PCR system by using the orthogonal design method and the annealing temperature of the PCR reactions was also optimized. Finally, a multiplex PCR system for the simultaneous detection of these three pathogens of maize was successfully established. The reaction volume was 25 μl and the annealing temperature was 57℃. The optimal conditions for multiplex PCR reaction contained 0.48 μmol/L Cl‐1/Cl‐2, 0.72 μmol/L Bm‐1/Bm‐2, 0.24 μmol/L Az‐1/Az‐2, 1.5 U polymerase, 0.35 mmol/L dNTP, and 1.25 mmol/L MgCl2 . The multiplex PCR system can detect Curvularia lunata, Bipolaris maydis, and Aureobasidium zeae in infected plant tissues rapidly with the sensitivity at 10 pg DNA/μl.